KfW/ZEW CO2 Barometer 2013 – Carbon Edition. The EU Emissions Trading Scheme: Firm Behaviour During the Crisis - Andreas Löschel; Carlo Gallier; Benjamin Lutz; Karl Ludwig Brockmann; Caroline Dieckhöner (KfW Bankengruppe und Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
The KfW/ZEW CO2 Barometer – developed as part of a cooperative project of KfW Bankengruppe and the Centre for European Economic Research (ZEW) – has been analyzing the situation of German companies regulated under the European Union Emissions Trading System (EU ETS) on an annual basis since 2009. The study's objective is to closely monitor firm behavior in carbon markets in order to regularly provide detailed information to policy-makers, businesses and the research community. For that purpose, all German firms regulated under the EU ETS, are invited to participate in the survey every year. On average, approximately 140 companies of 800 have responded to the questionnaire per year. The results are reported in an annual publication, the KfW/ZEW-CO2-Barometer – Carbon Edition. Main Results of the Survey: The Low CO2-Emission Price in the European Emissions Trading System (EU ETS) Barely Leads to CO2 Avoidance. Trading Volumes of Regulated Companies Are Increasing. Firms Expect Only a Decent Recovery of the CO2-Emission Price for the Next Year. Emissions in Germany Are Increasing Whereas Europe in Total Experiences Downswing.
Keywords: 330